Re-Challenge with Sonidegib after Vismodegib Discontinuation in a Near- Centenarian Patient with Locally Advanced Basal Cell Carcinoma - C, Di Raimondo; A, Petruzzellis; FS, Maramao; P, Lombardo; F, Lozzi; E, Campione; L, Bianchi (Archives of Clinical and Medical Case Reports, 2022)
Abstract not available in the source database.